The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2196/24080
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Mobile Health–Based Exercise Interventions for Patients with Peripheral Artery Disease: Systematic Review and Meta-Analysis

Abstract: Background Peripheral artery disease (PAD) affects over 236 million people worldwide, and exercise interventions are commonly used to alleviate symptoms of this condition. However, no previous systematic review has evaluated the effects of mobile health (mHealth)–based exercise interventions for patients with PAD. Objective This study aimed to assess the effect of mHealth-based exercise interventions on walking performance, functional status, and qualit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…It also facilitates the tracking of activity, behavior, and weight, allowing for real-time recording, feedback, and accountability [ 27 ]. Previous studies have shown that mHealth technologies support a reduction in obesity, improving physical activity and reducing the risk of developing life-threatening complications [ 28 - 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also facilitates the tracking of activity, behavior, and weight, allowing for real-time recording, feedback, and accountability [ 27 ]. Previous studies have shown that mHealth technologies support a reduction in obesity, improving physical activity and reducing the risk of developing life-threatening complications [ 28 - 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The percentages of participants who showed difficulty in walking a distance of 200 m, walking at an average speed, and climbing three flights of stairs were 37.7%, 54.7%, and 59.4%, respectively. According to previous meta-reviews, structured exercise interventions improved objective walking performance and subjective functional status [13,33]. Therefore, to improve the HRQOL for PAD patients, healthcare providers should establish strategies to improve walking performance and subjective functional status through structured exercise interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of supervision can range from directly monitoring the exercise in person, to facilitating a programme with scheduled check-ins, to an absence of any supervision. Frequency of in-person check ins can range from weekly to monthly, and more recently, remote check ins via telephone or video calls have been implemented [2,[11][12][13][14]. The COVID-19 pandemic has not only highlighted the need for this remote option, but also participant receptivity to such methods by alleviating for example time and travel burdens.…”
Section: Deliverymentioning
confidence: 99%